Chemical tuning of photoswitchable azobenzenes: a photopharmacological case study using nicotinic transmission - Sansalone, Lorenzo; Zhao, Jun; Richers, Matthew T.; Ellis-Davies, Graham C. R. (Beilstein Journal of Organic Chemistry, 2019)
We have developed photochromic probes for the nicotinic acetylcholine receptor that exploit the unique chemical properties of the tetrafluoroazobenzene (4FAB) scaffold. Ultraviolet light switching and rapid thermal relaxation of the metastable cis configuration are the main drawbacks associated with standard AB-based switches. We designed our photoprobes to take advantage of the excellent thermodynamic stability of the cis-4FAB configuration (thermal half-life > 12 days at 37 °C in physiological buffer) and cis–trans photostationary states above 84%. Furthermore, the well-separated n–π* absorption bands of trans- and cis-4FAB allow facile photoswitching with visible light in two optical channels. A convergent 11-step synthetic approach allowed the installation of a trimethylammonium (TA) head onto the 4FAB scaffold, by means of an alkyl spacer, to afford a free diffusible 4FABTA probe. TAs are known to agonize nicotinic receptors, so 4FABTA was tested on mouse brain slices and enabled reversible receptor activation with cycles of violet and green light. Due to the very long-lived metastable cis configuration, 4FAB in vivo use could be of great promise for long term biological studies. Further chemical functionalization of this 4FAB probe with a maleimide functionality allowed clean cross-linking with glutathione. However, attempts to conjugate with a cysteine on a genetically modified nicotinic acetylcholine receptor did not afford the expected light-responsive channel. Our data indicate that the 4FAB photoswitch can be derivatized bifunctionally for genetically-targeted photopharmacology whilst preserving all the favorable photophysical properties of the parent 4FAB scaffold, however, the tetrafluoro motif can significantly perturb pharmacophore–protein interactions. In contrast, we found that the freely diffusible 4FABTA probe could be pre-set with green light into an OFF state that was biologically inert, irradiation with violet light effectively "uncaged" agonist activity, but in a photoreversible manner. Since the neurotransmitter acetylcholine has fully saturated heteroatom valences, our photoswitchable 4FABTA probe could be useful for physiological studies of this neurotransmitter.
Keywords: acetylcholine receptors; bidirectional; photoswitchable drug; tetrafluoroazobenzene; visible light

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Kaufman, H.; Vratsanos, S. M.; Erlanger, B. F. (Science, 1968)

(untitled) - Bartels, E.; Wassermann, N. H.; Erlanger, B. F. (Proc. Natl. Acad. Sci. U. S. A., 1971)

(untitled) - Lester, H. A.; Krouse, M. E.; Nass, M. M.; Wassermann, N. H.; Erlanger, B. F. (Nature, 1979)

(untitled) - Lester, H. A.; Krouse, M. E.; Nass, M. M.; Wassermann, N. H.; Erlanger, B. F. (J. Gen. Physiol., 1980)

(untitled) - Nargeot, J.; Lester, H. A.; Birdsall, N. J.; Stockton, J.; Wassermann, N. H.; Erlanger, B. F. (J. Gen. Physiol., 1982)

(untitled) - Kumita, J. R.; Smart, O. S.; Woolley, G. A. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Fehrentz, T.; Schönberger, M.; Trauner, D. (Angew. Chem., Int. Ed., 2011)

(untitled) - Lerch, M. M.; Hansen, M. J.; van Dam, G. M.; Szymanski, W.; Feringa, B. L. (Angew. Chem., Int. Ed., 2016)

(untitled) - Dong, M.; Babalhavaeji, A.; Samanta, S.; Beharry, A. A.; Woolley, G. A. (Acc. Chem. Res., 2015)

(untitled) - Bléger, D.; Hecht, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Bléger, D.; Schwarz, J.; Brouwer, A. M.; Hecht, S. (J. Am. Chem. Soc., 2012)

(untitled) - Knie, C.; Utecht, M.; Zhao, F.; Kulla, H.; Kovalenko, S.; Brouwer, A. M.; Saalfrank, P.; Hecht, S.; Bléger, D. (Chem. – Eur. J., 2014)

(untitled) - Passlick, S.; Richers, M. T.; Ellis-Davies, G. C. R. (Angew. Chem., Int. Ed., 2018)

(untitled) - Durand-de Cuttoli, R.; Mondoloni, S.; Marti, F.; Lemoine, D.; Nguyen, C.; Naude, J.; d'Izarny-Gargas, T.; Pons, S.; Maskos, U.; Trauner, D.; Kramer, R. H.; Faure, P.; et al. (eLife, 2018)

(untitled) - Tochitsky, I.; Banghart, M. R.; Mourot, A.; Yao, J. Z.; Gaub, B.; Kramer, R. H.; Trauner, D. (Nat. Chem., 2012)

(untitled) - Damijonaitis, A.; Broichhagen, J.; Urushima, T.; Hüll, K.; Nagpal, J.; Laprell, L.; Schönberger, M.; Woodmansee, D. H.; Rafiq, A.; Sumser, M. P.; Kummer, W.; Gottschalk, A.; et al. (ACS Chem. Neurosci., 2015)

(untitled) - Cabré, G.; Garrido-Charles, A.; Moreno, M.; Bosch, M.; Porta-de-la-Riva, M.; Krieg, M.; Gascón-Moya, M.; Camarero, N.; Gelabert, R.; Lluch, J. M.; Busqué, F.; Hernando, J.; et al. (Nat. Commun., 2019)

(untitled) - Banghart, M.; Borges, K.; Isacoff, E.; Trauner, D.; Kramer, R. H. (Nat. Neurosci., 2004)

(untitled) - Volgraf, M.; Gorostiza, P.; Numano, R.; Kramer, R. H.; Isacoff, E. Y.; Trauner, D. (Nat. Chem. Biol., 2006)

(untitled) - Wu, D.; Dong, M.; Collins, C. V.; Babalhavaeji, A.; Woolley, G. A. (Adv. Opt. Mater., 2016)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Shih, P.-Y.; Engle, S. E.; Oh, G.; Deshpande, P.; Puskar, N. L.; Lester, H. A.; Drenan, R. M. (J. Neurosci., 2014)